2019
DOI: 10.1177/1077801219888025
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Bystanders Witnessing Cyber Violence Against Women and Girls: What They Observe and How They Respond

Abstract: The widespread use of social networks has turned cyber violence into a serious problem. We performed a survey with 1,468 adolescents aged 13-17 years and found that almost one in four frequently observed different forms of cyber violence against women and girls. More than a third of the adolescents who witnessed the violence did nothing, and while girls gave more active responses to help the victim, both girls and boys normalized and even justified this behavior. Our findings also underline how little is known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 29 publications
0
15
0
4
Order By: Relevance
“…These results suggest that adolescents rarely turn to their parents or other adults for concerns and issues related to DV and indicate that friends may play a crucial function as protective figures in DV, mostly among girls [50,51]. Nevertheless, another study found that adolescents who suffered online DV tended to seek support first from parents than from peers or teachers, especially in the case of girls [52].…”
Section: Social Context Perceived Attachment To Parents and Peers And Adolescent/young Adults Dating Violencementioning
confidence: 91%
“…These results suggest that adolescents rarely turn to their parents or other adults for concerns and issues related to DV and indicate that friends may play a crucial function as protective figures in DV, mostly among girls [50,51]. Nevertheless, another study found that adolescents who suffered online DV tended to seek support first from parents than from peers or teachers, especially in the case of girls [52].…”
Section: Social Context Perceived Attachment To Parents and Peers And Adolescent/young Adults Dating Violencementioning
confidence: 91%
“…The studies included in this study were published between the years of 2010 (Mishna et al 2010) and 2020 (Buelga et al 2020;Caridade et al 2020;Galende et al 2020;Jun 2020;Rebollo-Catalan and Mayor-Buzon 2020;Reed et al 2016). The year with the most publications was 2020 (n = 6), followed by 2018 (n = 3) and 2019, and 2017 and 2015 (n = 2).…”
Section: Year Of Publication and Locationmentioning
confidence: 99%
“…The year with the most publications was 2020 (n = 6), followed by 2018 (n = 3) and 2019, and 2017 and 2015 (n = 2). Most of the studies were conducted in Spain (n = 4) (Buelga et al 2020;Galende et al 2020;Rebollo-Catalan and Mayor-Buzon 2020;Sánchez et al 2015). Three studies were conducted in Portugal (Caridade et al , 2020Pereira et al 2016), and three included several countries (Athanasiou et al 2018;Del Rey et al 2015).…”
Section: Year Of Publication and Locationmentioning
confidence: 99%
“…Adölesan dönemdeki bireylerle yapılan bir araştırmada, kadıtımcıların %24'ünün siber şiddeti sıklıkla gözlemlediği, en yaygın olarakta partnerin sosyal medyadaki etkinliğini izlemek ve telefon kullanımını incelemek olduğu saptanmıştır. Ayrıca çalışmada siber şiddeti gözlemleyenlerin üçte birinin pasif davrandığı ve tepki vermediği belirlenmiştir (Rebello-Catalan ve Mayor-Buzon, 2020, s.2031-2037.…”
Section: Dijital Dünyada Kadına Yönelik şIddetunclassified